TUBERCULOSIS IN CHILDREN IN THE RUSSIAN FEDERATION AT THE PRESENT STAGE - A. V. Mordyk; E. A. Tsygankova; L. V. Puzyryova; A. A. Turitsa (Педиатрическая фармакология)
The literature review presents data on peculiarities of tuberculosis epidemiology, incidence rate and clinical pattern in children in the Russian Federation. Over the last 5 years, the age structure of the children developing tuberculosis has significantly changed: the share of children of small and preschool age increased, whereas the share of 7-14-year-old children decreased. Tuberculosis of thoracic lymph nodes predominates in the structure of clinical forms of tuberculosis of respiratory organs in children; small forms predominate, which indicates improvement of diagnostic capabilities. However, a rather large number of children with calcination stage of the tubercular process is observed. Further improvement of early detection of a tubercular infection is a powerful tool of preventing complicated and progressive forms of tuberculosis in children.